RANCANG BANGUN SISTEM INFORMASI PEMESANAN KATERING BERBASIS WEB (Studi Kasus Pada Katering Jelita) - Rahman Prehanto, Dedy; Lailatul Fitriah, Maya (Inovate, 2016)
Catering fairest is an undertaking in the fields of food service who handles reserving food .To performfood customers reservations required to come directly into place a caterer in order to obtain the informationneeded . This application is expected to be can expanding network marketing on catering fairest as well asproviding an alternative for customers in transact reservations.This final, writer built a system of using a web reservations. Web subscribers will more readily intransact reserving, because of reservations can be done anywhere and anytime without having to dating caterer.all the wayOther benefits also can be perceived by of admin, with using a web of admin can be more easilyaccess data reserving without having seen a record book reservations or computer who are outta my officecatering. The result of this research is that a system based on the web, the implements of programming to solvethe reservations which uses the internet links between providers and consumers. Key word : catering , the the information system , web